After the massacre commemoration and consolation in Ha My and My Lai - Gwon, Heon ig 1962- (Asia - local studies/global themes, 2006)
Though a generation has passed since the massacre of civilians at My Lai, the legacy of this tragedy continues to reverberate throughout Vietnam and the rest of the world. This text considers how Vietnamese villagers have assimilated the catastrophe of these mass deaths into their everyday ritual lives.